Islamic Religious Counselors' Strategies and Challenges in Promoting Family Harmony: A Case Study in the Socio-Culturally Diverse Rural Context of Hinai Subdistrict-Indonesia - Putra, Ardika Mandala; Sikumbang, Ahmad Tamrin (Universitas Nurul Jadid, 2025)
A harmonious family serves as a foundational pillar in fostering a stable and prosperous society. This study investigates the roles, strategies, challenges, and impacts of Islamic religious counselors in promoting family harmony in Tanjung Mulia Village, Hinai Subdistrict, Langkat Regency—an area marked by socio-cultural diversity and limited access to formal state services. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation involving the Head of KUA, religious counselors, village leaders, and married couples. Data analysis followed the Miles and Huberman model, involving data reduction, display, and conclusion drawing, with triangulation and peer review ensuring validity and reliability. Findings reveal that counselors serve not only as spiritual advisors but also as social facilitators and informal psychological support agents. Structured programs such as BRUS (School-Age Youth Guidance), BRUN (Marriage-Age Youth Guidance), and post-marriage counseling address mental, emotional, and spiritual readiness for family life. Strategies include five stages: planning, task distribution, implementation, evaluation, and reporting. Counseling is conducted in schools, prisons, mosques, and community centers, reflecting adaptability and reach. Key challenges include limited funding, low community literacy, inadequate infrastructure, and weak inter-agency collaboration. Nevertheless, the programs yield positive outcomes, such as improved spousal communication, enhanced role understanding, and reduced early marriage. Compared to formal state services, religious counselors provide grassroots, preventive family support that fills critical gaps. To optimize impact, this study recommends: (1) integrating counseling with national family programs, (2) enhancing counselor training in psychosocial and gender-sensitive skills, and (3) funding local-level initiatives. These findings offer transferable models for similar rural contexts.